PERTUMBUHAN TANAMAN SAMAMA (Anthocephallus macrophylla) PADA TANAH ALUVIAL DI DESA URSANA KECAMATAN INAMOSOL KABUPATEN SERAM BAGIAN BARAT - Matinahoru, Johan Markus (MARSEGU : Jurnal Sains dan Teknologi, 2025)
Samama (Anthocephallus macrophylla) is a type of forest tree found growing naturally ecologically this type of tree also likes secondary forest areas that are quite open to sunlight. Several field observations obtained that samama trees also like to grow in areas on the banks or around rivers that are dominated by alluvial soil with sufficient organic matter content. Alluvial soil is very suitable for cultivating samama plants because it produces good average growth in diameter and free branch height. Environmental factors such as soil fertility, soil moisture, soil acidity, temperature, air humidity and light intensity have a very significant effect on the growth of samama plants.